2011
DOI: 10.1007/s10549-011-1902-7
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol promotes mammary tumor growth and angiogenesis: the involvement of chemoattractant factor MCP-1

Abstract: Alcohol consumption is a risk factor for breast cancer in humans. Experimental studies indicate that alcohol exposure promotes malignant progression of mammary tumors. However, the underlying cellular and molecular mechanisms remain unclear. Alcohol induces a pro-inflammatory response by modulating the expression of cytokines and chemokines. Monocyte chemoattractant protein-1 (MCP-1), also known as chemokine (C-C motif) ligand 2 (CCL2), is a pro-inflammatory chemokine implicated in breast cancer development/ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
77
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(82 citation statements)
references
References 31 publications
5
77
0
Order By: Relevance
“…In that study, ethanol promoted angiogenic activity in human umbilical vein endothelial cells by stimulating a novel Notch/Angiopoietin-1 pathway [5]. These in vitro data, and the new data in human coronary artery endothelial cells presented here, are in general agreement with the in vivo studies mentioned above demonstrating a stimulatory effect of alcohol consumption on myocardial neovessel development [26, 27] and with several other studies reporting a stimulatory effect of EtOH on angiogenesis, some looking at tumor angiogenesis [29] [30] [31] [13]. At least one group describes an inhibitory effect of EtOH on angiogenesis in the context of wound healing [14] [32].…”
Section: Discussionsupporting
confidence: 90%
“…In that study, ethanol promoted angiogenic activity in human umbilical vein endothelial cells by stimulating a novel Notch/Angiopoietin-1 pathway [5]. These in vitro data, and the new data in human coronary artery endothelial cells presented here, are in general agreement with the in vivo studies mentioned above demonstrating a stimulatory effect of alcohol consumption on myocardial neovessel development [26, 27] and with several other studies reporting a stimulatory effect of EtOH on angiogenesis, some looking at tumor angiogenesis [29] [30] [31] [13]. At least one group describes an inhibitory effect of EtOH on angiogenesis in the context of wound healing [14] [32].…”
Section: Discussionsupporting
confidence: 90%
“…Alcohol consumption is consistently associated with the risk of breast cancer (Deandrea et al ., 2008; MacMahon, 2006; Suzuki et al ., 2008). Alcohol feeding prompted mammary tumor formation (Wang et al ., 2012; Wong et al ., 2012). Our studies have demonstrated that alcohol increases Brf1 expression and Pol III gene transcription to facilitate cell transformation and tumor formation (Zhang et al ., 2013; Zhong et al ., 2011, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol increases Brf1 expression to upregulate Pol III gene transcription in vivo and in vitro (Zhang et al ., 2013; Zhong et al ., 2011). Studies have indicated that alcohol administration induces breast tumor formation of alcohol‐fed mice (Wang et al ., 2012; Wong et al ., 2012). This finding suggests that alcohol‐caused deregulation of Pol III genes is associated with mammary tumor development.…”
Section: Introductionmentioning
confidence: 99%
“…The protocol was approved by the Mayo Clinic Foundation Institutional Review Board for Human Research. Detailed descriptions of our preadipocyte, HUVEC, IMR90, and MEF culture methods are in Data S1 (Supporting information) and publications (Tchkonia et al ., 2007; Wang et al ., 2012). …”
Section: Methodsmentioning
confidence: 99%